Multi-layered nanosystems for the controlled release of anticancer drugs - Carvalho, João Pedro Fernandes (2018)
Cancer is one of the leading causes of death worldwide, and current therapeutic options present numerous drawbacks. Chemotherapy, specifically, is associated with widely known side effects. However, and due to the scientific and technologic advances of the past years, a new approach to this dilemma appears in nanomedicine: the use of nanosystems capable of releasing the anticancer drugs in a controlled way and only at the designated cells. These nanosystems may be obtained from numerous materials, including biopolymers, and by various techniques. Specifically, the work described here consists in the synthesis and characterization of nanoparticles obtained by layer-by-layer assembly from amino-modified spherical SiO2 templates (diameter: 234 ± 19 nm). The alternate deposition of biopolymers - alginate (ALG) and chitosan (CH) or lysozyme nanofibrils (LNFs) - on templates pre-loaded with curcumin allowed the creation of nanoparticles covered in ALG/CH (with a diameter of 243 ± 8 nm) or ALG/LNFs (with 242 ± 8 nm). The systematic reversion the zeta-potential and the observation of the particles by scanning electron microscopy (SEM) confirms the deposition of each biopolymeric layer. The present work also includes the evaluation of the release profile of this drug from the multi-layered nanoparticles, demonstrating a more controlled release than with the bare counterparts. The evaluation of their cytotoxic capacity in human liver cancer cell line (HepG2) was posteriorly evaluated through an MTT assay. The cytotoxic effect of layered particles containing CUR was similar to the unlayered counterparts’, demonstrating that the two layers of biopolymers (ALG/CH or ALG/LNFs) do not compromise their cytotoxic potential.